Assessing governance of irrigation systems: A view from below. (September 2020) - Akuriba, Margaret Atosina; Haagsma, Rein; Heerink, Nico; Dittoh, Saa
Highlights: Measuring governance, and explaining it, is crucial for improving the performance of irrigation schemes. Ratings provided by local water users are used to assess the governance of small-scale irrigation schemes. Six different dimensions of governance are distinguished. Sustainable use received the lowest score and conflict management the highest score. Head-end users and tail-end users gave lower scores than users that had plots in the middle. Abstract: Attempts at irrigation development in Ghana, as in many other parts of sub-Saharan Africa, have been characterized by governance challenges at various levels. This paper aims to provide an empirical assessment of irrigation governance in 37 small-scale irrigation schemes in northern Ghana, derived from the perceptions of their users. We first distinguish six dimensions of governance based on the available literature to include participation, accountability, conflict management, transparency and cooperation, equity and fairness, and sustainable use. Next, we measure these irrigation governance dimensions using ratings provided by local water users. We then examine the relationship between these governance measures and some objective factors that possibly drive the assessments of users. The results indicate an overall good governance in the sampled schemes. Relatively, sustainable use had the lowest score and conflict management had the highest score. We further find that in schemes located in areas with relatively high annual precipitations, users report better irrigation governance. Within schemes, both users with plots at the head end and users with plots at the tail end are more critical about irrigation governance than other users. Remarkably, the number of users of a scheme has no significant effect on their overall assessment of its governance, although users in larger schemes are more positive on opportunities to participate in governance bodies and to keep these bodies accountable. To improve their sustainability, small-scale irrigation schemes (dams) may be better maintained for domestic and livestock watering. Promoting water-conserving irrigation techniques such as drip irrigation and ground water techniques is essential.